Greening aid? - Robert L. Hicks (Oxford University Press, 2008)
Every year, billions of dollars of environmental aid flow from the rich governments of the North to the poor governments of the South. Why do donors provide this aid? What do they seek to achieve? How effective is the aid given? And does it always go to the places of greatest environmental need?